Emerging sectarianism in the Dead Sea scrolls: continuity, separation, and conflict - Collins, John J.; Geyser-Fouché, Ananda (Studies on the texts of the desert of Judah, 2022)
The essays in this volume consider the nature of the sect known from the Scrolls and its relation to mainline Judaism. Especially notable is a cluster of essays dealing with the Teacher and a review of the archaeology of Qumran